2023
DOI: 10.3390/pathogens12030452
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations of the Monkeypox Virus: A Systematic Review and Meta-Analysis

Abstract: Background: The accurate estimation of the prevalence of mpox-induced ophthalmic lesions will enable health departments to allocate resources more effectively during the ongoing mpox pandemic. The aim of this meta-analysis was to estimate the global prevalence of ophthalmic manifestations in mpox patients. Methods: A systematic search was carried out in seven databases—Pub Med, Scopus, Web of Science, EMBASE, ProQuest, EBSCOHost, and Cochrane—for studies published on or before 12 December 2022. The pooled prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A total of 776 articles were yielded in the systematic search from different databases such as Cochrane (1), EBSCOHost-Academic Search Complete (123), EMBASE (8), ProQuest (5), PubMed (208), Scopus (192), Web of science (27), preprint servers such as medRxiv, arXiv, bioRxiv, BioRN, ChiRxiv, ChiRN and SSRN (3), and Google Scholar (209). Among them, 199 duplicate studies were excluded.…”
Section: Search and Screening Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 776 articles were yielded in the systematic search from different databases such as Cochrane (1), EBSCOHost-Academic Search Complete (123), EMBASE (8), ProQuest (5), PubMed (208), Scopus (192), Web of science (27), preprint servers such as medRxiv, arXiv, bioRxiv, BioRN, ChiRxiv, ChiRN and SSRN (3), and Google Scholar (209). Among them, 199 duplicate studies were excluded.…”
Section: Search and Screening Resultsmentioning
confidence: 99%
“…Graphical display of study heterogeneity (GOSH) plot analysis [K-means, Density-Based Spatial Clustering of Applications with Noise (DBSCAN), Gaussian] was also undertaken to identify the outliers, and a pooled estimate was arrived at after removing all the outliers, simultaneously. Heterogeneity was explored by means of subgroup analysis (27) according to the type of population (refugee & IDPs) and geographical origin of the refugees. The mixed effect model has been used for subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After the title abstract selection, 170 articles were eligible for full-text selection. In the full-text screening, 139 articles were excluded due to non-reporting of HIV status (96), incorrect study design (27), and incorrect patient population (16). Two new studies were included from the hand-search of the references from the included studies.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…The epidemiological profile of mpox has shown considerable variation between continents, endemic/nonendemic countries, and the period of the cases (2022 multicountry outbreak vs. Pre-2022) in terms of mortality rates, clinical manifestations, and demographic characteristics of the affected population [ 14 , 15 , 16 , 17 ]. Studies in Africa before the current outbreak reported a prevalence of HIV among mpox in the range of 18.75% to 25%[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of mpox infection are mostly characterized by headaches, fever, chills, fatigue, myalgia, flu-like symptoms, skin lesions/rash, and lymphadenopathy. However, in the recent outbreak, atypical patterns of clinical symptoms have been reported in many cases ( Huhn et al., 2005 ; Satapathy et al., 2022 ; Thornhill et al., 2022a ; Gandhi AP. et al., 2023 ; Gandhi PA. et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%